Comparative Invitro Antioxidant Activty of Pongamia pinnata Linn. Leaves Extracts and Isolated Compound - porwal, piyush (International Journal of Pharmaceutical & Biological Archive, 2010)
The word herb, as used in herbal medicine, is also known as botanical medicine or as phytotherapy or phytomedicine which means a plant or plant part is used to make medicine to assist in the healing process during illness and disease. Pongamia pinnata Linn. Pierre commonly known as ‘Karanj’ has been used in different system of traditional medicines for the treatment of various diseases. It contains various phytoconstituents belonging to alkaloids, glycosides, flavonoids, fixed oils and carbohydrates. The roots of Pongamia pinnata are good for cleaning foul ulcers, cleaning teeth, strengthening gums and gonorrhoea. The root paste is used for local application in scrofulous enlargement. The fresh bark of Pongamia pinnata is sweet and mucilaginous to taste, soon become bitter and acrid. It is anthelmintic and is useful in beriberi, ophthalmology, dermatopathy, vaginopathy and ulcers. Leaves of Pongamia pinnata are digestive, laxative, anthelmintic and are good for diarrhoea, leprosy, dyspepsia and cough. A hot infusion of leaves is good for cleaning ulcers and wounds. Flowers are useful to quench dipsia in diabetes and for alleviating vata and kapha. The seeds are anthelmintic, bitter, acrid, haematinic and carminative. They are useful in inflammation, chronic fevers, anaemia and haemorrhoids. The oil is anthelmintic, styptic and recommended for ophthalmia, leprosy, ulcers, herpes and lumbago. Its oil is a source of biodiesel. Our aim with this study was to evaluate the antioxidant properties of Pongamia pinnata. The antioxidant activity of isolated compound and various extracts of Pongamia pinnata was evaluated in vitro by DPPH free radical scavenging activity. Our results showed that Pongamia pinnata displayed potent antioxidant properties, supporting the ethnomeidcal use given to this plant for treatment of diseases.